The Collaborative Role Of Health Administrators, Security Specialists, Ems Technicians, Diagnostic Radiologists, And Health Assistants In Optimizing Mri And Ct Use For Early Acute Stroke Detection In Saudi Military, Civilian, And Cluster Hospital Settings (The Review of Diabetic Studies, 2025)
Acute ischemic stroke represents a neurological emergency requiring rapid diagnostic imaging to guide time-sensitive interventions. The effectiveness of computed tomography and magnetic resonance imaging in stroke detection depends substantially on coordinated collaboration among diverse healthcare professionals. This systematic review examines the interprofessional roles of health administrators, security specialists, emergency medical services technicians, diagnostic radiologists, and health assistants in optimizing neuroimaging utilization for acute stroke diagnosis within Saudi Arabian military, civilian, and cluster hospital contexts. A comprehensive literature search across PubMed, Scopus, Web of Science, and regional databases identified peer-reviewed publications addressing stroke imaging protocols, interprofessional collaboration frameworks, and healthcare system characteristics specific to Saudi Arabia. Analysis of 43 included studies revealed that systematic coordination among these professional groups significantly reduces door-to-imaging time, enhances diagnostic accuracy, and improves patient outcomes. Health administrators establish protocols and resource allocation strategies; security personnel facilitate rapid patient movement; EMS technicians provide prehospital notification and triage; radiologists ensure imaging quality and interpretation; while health assistants coordinate logistics and documentation. Implementation barriers include communication gaps, training deficits, and infrastructure limitations particularly evident in resource-constrained settings. This review synthesizes evidence supporting integrated care pathways and proposes recommendations for strengthening interprofessional collaboration in Saudi healthcare environments to optimize acute stroke management.